Understanding the fall-related safety issues in concrete formwork - Chellappa Vigneshkumar; Ravindra Salve Urmi (E3S Web of Conferences, 2021)
The construction industry recorded high rates of fatalities and injuries due to falls at the workplace. Among other activities, concrete formwork tends to have more fatal falls. This study aims to understand the fall-related safety issues in the formwork lifecycle of construction projects. To achieve this, the process of formwork activities was mapped, and the safety risks associated with each activity were classified. Method development and risk identification focused on interviews with construction professionals involved in the construction of formwork and site observations of the formwork activities. The overall finding was that pouring, stripping, and erection activities have more issues related to falls. Future research is being carried out to assess the risks of falls from the construction experts’ views to prevent fall accidents in the future.